The Role of Public Administration Expenditures in Tourism Development - Tufănoiu, Ionuț; Toma, Cristina (European Journal of Sustainable Development, 2024)
This study examines the relationship between public administration expenditure and the development of the tourism sector in four Administrative Territorial Units (ATUs) with high natural potential between 2000 and 2018. It first analyzes the public expenditures of the ATUs, classifying them by function and calculating the share of each expenditure in the total. Next, the study assesses local economies using the Classification of National Economic Activities (NACE) to determine the contribution of tourism. Finally, the two databases are correlated to explore the impact of public spending on tourism growth. The findings provide a foundation for developing new methodologies to assess public investment in tourism and raise awareness of its importance. Keywords: tourism, revenues, expenditures, public administration, local economy